HIV disclosure, condom use, and awareness of HIV infection among HIV-positive, heterosexual drug injectors in St. Petersburg, Russian Federation. - Grau, Lauretta E; White, Edward; Niccolai, Linda M; Toussova, Olga V; Verevochkin, Sergei V; Kozlov, Andrei P; Heimer, Robert (AIDS and behavior, 2011)
We examined the prevalence of HIV disclosure to sexual partners by HIV-positive drug injectors (IDUs) in St. Petersburg, Russia and compared the magnitude and direction of associations of condom use with awareness of one's HIV infection and disclosure to partners. Among 157 HIV-infected participants, awareness of infection at time of last intercourse was associated with condom use with partners perceived to be HIV-negative (aOR 6.68, 95% CI 1.60-27.88). Among the 70 participants aware of their infection prior to enrolment, disclosure to potentially uninfected sexual partners was independently and negatively associated with condom use (aOR 0.13, 95% CI 0.02-0.66). Disclosure was independently associated with having injected ≥ 9 years (aOR 6.04, 95% CI 1.53-23.77) and partnership with another IDU (aOR 3.61, 95% CI 1.44-9.06) or HIV-seropositive (aOR 45.12, 95% CI 2.79-730.46). Scaling up HIV testing services and interventions that increase the likelihood of individuals receiving their test results is recommended.
Keywords: Adult; Condoms; Cross-Sectional Studies; Drug Users; Female; Health Knowledge, Attitudes, Practice; Heterosexuality; HIV Infections; HIV Seropositivity; HIV-1; Humans; Male; Middle Aged; Prevalence; Risk Factors; Russia; Self Disclosure; Sexual Partners; Socioeconomic Factors; Substance Abuse, Intravenous; Young Adult